Cardiac geometry, as assessed by cardiac magnetic resonance, can differentiate subtypes of chronic thromboembolic pulmonary vascular disease - McGettrick, Michael; Dormand, Helen; Brewis, Melanie; Johnson, Martin K.; Lang, Ninian N.; Church, Alistair Colin (Frontiers in Cardiovascular Medicine, 2022)
Background: Ventricular septal flattening reflects RV pressure overload in pulmonary arterial hypertension. Eccentricity index (EI) and pulmonary artery distensibilty (PAD) correlate with pulmonary artery pressure. We assessed the utility of these using cardiac magnetic resonance (CMR) to assess for pulmonary hypertension (PH) in patients with chronic thromboembolic disease. This may allow non-invasive differentiation between patients who have chronic thromboembolic pulmonary hypertension (CTEPH) and those with pulmonary vascular obstructions without PH at rest, known as chronic thromboembolic pulmonary disease (CTEPD). Methods: 20 patients without resting pulmonary hypertension, including 10 with chronic thromboembolic disease, and 30 patients with CTEPH were identified from a database at the Scottish Pulmonary Vascular Unit. CMR and right heart catheter had been performed within 96 hours of each other. Short-axis views at the level of papillary muscles were used to assess the EI at end-systole and diastole. Pulmonary artery distensibility was calculated using velocity-encoded images attained perpendicular to the main trunk. Results: EI at end-systole and end-diastole were higher in CTEPH compared to controls (1.3+/-0.5 vs 1.0+/-0.01; p=<0.01 and (1.22+/-0.2 vs 0.98+/-0.01; p=<0.01, respectively) and compared to those with CTED. PAD was significantly lower in CTEPH compared to controls (0.13+/-0.1 vs 0.46 +/-0.23;p=<0.01) and compared to CTED. End-systolic EI and end-diastolic EI correlated with pulmonary vascular haemodynamic indices and exercise variables, including mean pulmonary arterial pressure (R0.74 and 0.75, respectively), cardiac output (R-value -0.4 and -0.4, respectively) NTproBNP (R-value 0.3 and 0.3, respectively) and 6-minute walk distance (R-value-0.7 and -0.8 respectively). Pulmonary artery distensibility also correlated with 6-minute walk distance (R-value0.8). Conclusions: EI and PAD can detect the presence of pulmonary hypertension in chronic thromboembolic disease and differentiate between CTEPH and CTED subgroups. These measures support the use of non-invasive tests including CMR for the detection pulmonary hypertension and may reduce the requirement for right heart catheterisation.